WEWENANG KEPOLISIAN MENGADAKAN TINDAKAN LAIN DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP ANAK MENURUT UNDANG-UNDANG NO.11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - I Wayan Juwahyudhi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
ABSTRACTOne of the police authorities is a discretionary action, where the action can also be done at the time of the investigation in dealing the juvenile offenders to protect children’s right to get justice and maximum legal protection. In the Law Number 11 of 2012 on the Juvenile Criminal Justice System stipulate about the investigator authority to carry out action of diversion, but this only applies to children under sentence of less than 7 years in prison and does not apply in children who are subject to punishments of more than 7 years in prison. This is contrary to the 1945 Constitution and the Law Number 23 of 2002 which emphasizes the protection of children before the law an the efforts to avoid imprisonment of the juvenile offenders.The thesis describes the police authority and the legal mechanisms and policies by the investigator in protecting the right on the juvenile offenders that puts the principles of legal protection. In order to avoid negative effects on children, therefore the police discretion is needed to avoid restrictions on freedom of the children’s right. The method used is a normative legal research method, where the normative or library legal research method is done by examining existing library materials.The writer suggested to the government to be more serious in dealing with the problems of children, especially for the juvenile offenders so that the welfare and right of children are protected and to avoid restrictions on freedom and minimize for juvenile offenders.